ADAPTASI KOMUNITAS NELAYAN ANTAR ETNIK KEARAH PENINGKATAN KEHIDUPAN SOSIAL EKONOMI DAN KEAGAMAAN (Studi Kasus Etnik Melayu dan Jawa di Bengkalis) - Hurmain Hurmain (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2012)
Adaptation socialing to constitute man characteristic as being of social needs to condition of vicinity it in day-to-day life. In consequence, can't be avoided that man is each other with human another. Study that modestly it is show how perceives nationality can go away to loosen so face ry social factor, economy, culture, and religion. In extreme point, Bengkalis's economic factor that rich observable can settle all another factor. But in next wave apparently base one was required to make a abode social points, assess religion that facet and culture. It at a swoop tempts to observe back to how settlement that done byfisherman society at Bengkalis